1990
DOI: 10.1038/348073a0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a human DNA excision repair gene involved in group A xeroderma pigmentosum and containing a zinc-finger domain

Abstract: Xeroderma pigmentosum (XP) is an autosomal recessive disease, characterized by a high incidence of sunlight-induced skin cancer. Cells from people with this condition are hypersensitive to ultraviolet because of a defect in DNA repair. There are nine genetic complementation groups of XP, groups A-H and a variant. We have cloned the mouse DNA repair gene that complements the defect of group A, the XPAC gene. Here we report molecular cloning of human and mouse XPAC complementary DNAs. Expression of XPAC cDNA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
153
0
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(159 citation statements)
references
References 21 publications
3
153
0
3
Order By: Relevance
“…During NER, TFIIH is thought to be recruited to the damage site at an early step of the repair process (12)(13)(14). The initial recognition of DNA lesions is likely to involve a nucleoprotein⅐DNA complex consisting of XPA, a zinc finger protein with some specificity for UV-or chemical carcinogendamaged DNA (15)(16)(17)(18)(19), RPA (20 -24), and probably other factors. TFIIH may then be involved in the formation of a preincision complex through an interaction with the COOH terminus of XPA (25).…”
mentioning
confidence: 99%
“…During NER, TFIIH is thought to be recruited to the damage site at an early step of the repair process (12)(13)(14). The initial recognition of DNA lesions is likely to involve a nucleoprotein⅐DNA complex consisting of XPA, a zinc finger protein with some specificity for UV-or chemical carcinogendamaged DNA (15)(16)(17)(18)(19), RPA (20 -24), and probably other factors. TFIIH may then be involved in the formation of a preincision complex through an interaction with the COOH terminus of XPA (25).…”
mentioning
confidence: 99%
“…Enhanced removal of LW-induced pyrimidine dimers lowers skin cancer rates in mice, indicating that unrepaired dimers cause cancer in mammalian skin (343). Individuals with the heritable syndrome Xeroderma pigmentosum (XP) have impaired ability to remove DNA lesions induced by UV and consequentially are extremely sensitive to UV exposure, which results in an increased risk of developing skin cancers (344)(345)(346)(347)(348)(349)(350)(351)(352)(353)(354)(355)(356)(357). Generation of mice deficient in XP genes have confirmed the important role these gene products play in protecting against UV-induced tumorigenesis (358)(359)(360) (362)(363)(364)(365)(366)(367)(368) [for review, see (369)].…”
Section: The Spindle Checkpointmentioning
confidence: 99%
“…However, recent studies (Guzder et al, 1995) have shown that the RAD14 gene contains an intron and the Rad14 protein actually contains 371 amino acid residues and has a molecular weight of 43 kDa. The amino acid sequence homology identifies the Rad14 protein as the human xeroderma pigmentosum (XPA) homologue, as does the existence of a putative CX 2 CX 18 CX 2 C zinc finger DNA binding motif (Tanaka et al, 1990;Bankmann et al, 1992): this motif is present in other eukaryotic XPA homologues which have been identified (Shimamoto et al, 1991).…”
Section: Introductionmentioning
confidence: 99%